2011
DOI: 10.1007/s10433-011-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Disability trends among nonagenarians in 2001–2007: Vitality 90+ Study

Abstract: Substantial growth of the population aged 90 years or over has focused interest on trends in the functioning and disability of the oldest old, but research findings are scarce and they vary. In the Vitality 90? Study, we evaluated overall, gender-specific, and agespecific trends in disability among total cohorts of people aged 90 years or older in the city of Tampere, Finland, in the years 2001, 2003, and 2007. The size of the target population ranged from 1113 to 1146 and the participation rate from 79 to 86%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…To include the most recent demographic data available, we accessed the Human Mortality Database. 3 In line with previous research, recent cohort comparisons 7,9,10,1820 reached differing conclusions about the health outcomes between cohorts, but the studies that used physical and cognitive testing generally focused on younger elderly people (age <85 years) and excluded those in residential care.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To include the most recent demographic data available, we accessed the Human Mortality Database. 3 In line with previous research, recent cohort comparisons 7,9,10,1820 reached differing conclusions about the health outcomes between cohorts, but the studies that used physical and cognitive testing generally focused on younger elderly people (age <85 years) and excluded those in residential care.…”
Section: Discussionmentioning
confidence: 78%
“…However, the sample size in both studies was small. 2426 A larger Finnish study 18 of nonagenarians in Tampere was based on a questionnaire survey and so did not include cognitive or physical tests, but the investigators reported stable frequencies of disability in 2001–07. In the USA, a series of analyses of data from the Health and Retirement Survey of people aged 70 years and older showed mixed results; Freedman and colleagues 27 reported improvement in cognitive functioning for individuals aged 80 years and older from 1993 to 1998, whereas Rodgers and colleagues 28 noted little improvement from 1993 to 2000 when age distribution and practice effect from previous study participation were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the Vitality 901 Study are collected by mailed surveys to the whole target population, face-to-face interviews, performance tests, blood samples with subgroups, and qualitative life story interviews (Jylhävä, Jylhä, Lehtimäki, Hervonen, & Hurme, 2012;Lisko et al, 2012;Sarkeala, Nummi, Vuorisalmi, Hervonen, & Jylhä, 2011). In 1996 and 1998, questionnaires were sent to community-dwelling inhabitants of Tampere and in the years 2001, 2003, 2007, and 2010 to every 90 years old and older persons in the area, irrespective of health or place of living.…”
Section: The Vitality 901 Studymentioning
confidence: 99%
“…It is a question of fact, for example, whether or not increasing life expectancy at older ages does indeed increase the risk of experiencing a prolonged period of serious cognitive impairment before death [17], and there is now a growing body evidence to suggest that life years with serious disability are not increasing [18,19]. It is also a question of fact whether or not the more effective implementation of current strategies for maximising the number of healthy life years in the average lifespan will have the desired outcome for end-of-life trajectories.…”
Section: The Dismal Viewmentioning
confidence: 99%